Assembling the Social and Political Dimensions of Take-Home Naloxone. (September 2017) - Farrugia, Adrian; Fraser, Suzanne; Dwyer, Robyn
Editor's Note: This issue of Contemporary Drug Problems features the first article in a new series entitled 'Contemporary Issues'. Articles commissioned for this series will be authored by emerging or established researchers and will address contemporary issues in theory and/or method, or those relating to a specific subfield or topic. The articles will be between 3–4, 000 words and will aim to set out key issues relating to a topic in a provocative but academically rigorous way. Publication turnaround is fast, allowing timely intervention in emerging debates and rapid access to our large readership. The first article, which appears below, is a thought-provoking piece on the emerging area of overdose prevention via take-home naloxone . Abstract: This commentary explores the complex position that take-home naloxone holds as a harm reduction strategy in contemporary public health contexts. Providing the opioid antagonist naloxone to people who consume opioids and others likely to witness opioid overdose is currently positioned as an exemplary lifesaving public health intervention. Few socially oriented studies of take-home naloxone raise questions beyond whether or not take-home naloxone "works"—lines of inquiry that we think should be raised. Until take-home naloxone efforts address harms as effects of social context and policy regimes, the focus on individual behavior change will constrain the equitable distribution of responsibility for tackling overdose and the capacity to achieve more ambitious harm reduction goals such as decriminalization and the associated destigmatization of those who consume opioids. We conclude by arguing for the analytic incorporation of issues of power and normalization that animate responses to opioid overdose, including take-home naloxone.